PEMBENTUKAN KULTUR AKHLAK MULIA DI KALANGAN MAHASISWA UNY MELALUI PEMBELAJARAN PAI - Marzuki Marzuki (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Noble Character Culture Building Among Students of Yogyakarta StateUniversity Through PAI Learning. This study aims to reveal problems in PAIlearning in Yogyakarta State University and its role in building students noblecharacter. This study was a qualitative study. The data were obtained throughinterviews, questionnaires, and documents and were analyzed using qualitativeanalysis techniques with the inductive approach. The results show that PAIlearning has an important role in building students noble character if supported bycompetent lecturers, good inputs, adequate materials, and good processes.Conversely, if such supports are not available, the goal will be difficult to attain.Among the problems are diverse student abilities, students less attention tocharacter, the emphasis of PAI learning materials on cognitive aspects, anddifficulty in controlling students outside the class.Keywords: culture building, noble character, PAI learning